MOBILE APPS FOR LEARNING ENGLISH - Parmankulova, D.R.; Kulayeva, S.S. (Educational Research in Universal Sciences, 2023)
Throughout and out of university, the use of technology has become an. Integral part of the learning process. Technology helps teachers to adapt lessons in the classroom, thereby improving the learning process, English as a second language/international. This paper discusses different attitudes which help English language learners by using technologies to increase their learning skills. Any recent studies have shown that mobile learning can provide potential possibilities for foreign language learners to practice language skills on their smart mobile phones The results indicated that mobile learning can be adopted in English lessons and students’ self-study. The app which provided sources related to lessons offered extra support to students to practice English in and after class.